Optimizing Healthcare Workflows through Technological Implementations - Tunk Raj Kiran; Priyanka Vallu; Ram Mohan Kasi; Srikanth Gunji (International Journal of Scientific Research in Science and Technology, 2024)
This research paper explores the implementation of various technological solutions to optimize healthcare workflows at Apollo Hospitals over a nine-month period from January 21st to October 11th. The initiatives include the deployment of Electronic Medical Records (EMR) software, Queue Management software, In-Patient Services software, Digital Coupons for Patients, Patient Identification Wrist-Band Stickers, and Smart Cameras in ambulances for patient vitals monitoring. These projects aimed to enhance patient care, improve operational efficiency, and increase patient satisfaction. Using the DMAIC model of Six Sigma, each project was systematically defined, measured, analyzed, improved, and controlled. The results demonstrate significant improvements in patient data management, queue handling, inpatient service efficiency, patient identification accuracy, and emergency response effectiveness. This study highlights the potential for technological advancements to transform healthcare delivery.
Keywords: Healthcare Workflow Optimization; EMR software; Queue Management; In-Patient Services; Patient Identification; Smart Cameras; DMAIC model; Six Sigma